Unfinished empire : the global expansion of Britain / John Darwin. - Darwin, John (Allen Lane, 2012)
In 'Unfinished Empire' John Darwin examines the enormous influence of the British Empire. It has shaped the world in countless ways: repopulating continents, carving out modern nations, imposing its own language, technology and values.